Misi Kehambaan Kristus Dalam Kinerja Pelayan Khusus - Suawa, Injilia J.; Ratag, Linda P. (UPT Penelitian Fakultas Teologi Universitas Kristen Indonesia Tomohon, 2024)
This article discusses the understanding of Special Servants (Deacons and Elders) regarding the mission of Christ's servanthood amidst the duties and responsibilities of Special Servants (Deacons and Elders) in the GMIM Solagratia Girian Weru Congregation, Bitung III Region. The research carried out by the author used qualitative research methods in which there were observations, interviews, and also library study techniques used for data collection needs. Christ's mission is based on the Biblical testimony of the Old and New Testaments as well as provision through the rules of service provided to Special Servants (Deacons and Elders) and always adapting them to the circumstances or conditions in which the congregation lives and works, namely how to be a serving servant. Based on the research results, it is suggested that Special Ministers (Deacons and Elders) should always be properly equipped and understand the mission work surrounding ministry and that there should be more emphasis on the importance of God's Mission in every aspect of life, including the attitude of servanthood in serving.